2013
DOI: 10.1242/dev.093500
|View full text |Cite
|
Sign up to set email alerts
|

Elastogenesis at the onset of human cardiac valve development

Abstract: Semilunar valve leaflets have a well-described trilaminar histoarchitecture, with a sophisticated elastic fiber network. It was previously proposed that elastin-containing fibers play a subordinate role in early human cardiac valve development; however, this assumption was based on data obtained from mouse models and human second and third trimester tissues. Here, we systematically analyzed tissues from human fetal first (4-12 weeks) and second (13-18 weeks) trimester, adolescent (14-19 years) and adult (50-55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 50 publications
(93 reference statements)
3
40
0
Order By: Relevance
“…To enable the process of elastogenesis, further proteins such as fibulins, elastin microfibril interface located protein 1 (EMILIN‐1), fibronectin, latent TGF‐beta binding protein 4 (LTBP‐4) are necessary . The process of elastogenesis is highly complex and still not completely understood; however, it has been shown that these events already play a major role in early human cardiovascular development . Therefore, when aiming for a nature‐mimicking highly functional biomaterial scaffold, elastic fibers and the elastic fiber‐associated proteins must be considered.…”
Section: Biomaterials Used For Blood Vessel Engineeringmentioning
confidence: 66%
“…To enable the process of elastogenesis, further proteins such as fibulins, elastin microfibril interface located protein 1 (EMILIN‐1), fibronectin, latent TGF‐beta binding protein 4 (LTBP‐4) are necessary . The process of elastogenesis is highly complex and still not completely understood; however, it has been shown that these events already play a major role in early human cardiovascular development . Therefore, when aiming for a nature‐mimicking highly functional biomaterial scaffold, elastic fibers and the elastic fiber‐associated proteins must be considered.…”
Section: Biomaterials Used For Blood Vessel Engineeringmentioning
confidence: 66%
“…Interestingly, several interstitial matrix proteins (COL5A2, COL12A1, COL26A1, EMID1, FBN1, FBLN5, ELN, THSD4) were significantly elevated or exclusively found at the perinatal timepoints, including components of the elastin-microfibril axis. [39][40][41] Overall, there was a significant decrease in interstitial matrix and a significant increase in basement membrane proteins over development ( Figure 4A). For example, the basement membrane proteins LAMA5 and NID1 were significantly increased at P3 compared to E14.5…”
Section: Resultsmentioning
confidence: 97%
“…The perinatal increase in abundance of these collagens and elastinmicrofibril axis proteins may provide mechanical integrity by transiently stabilizing the 3D fibrous medullary ray sheath and vertical fibers ( Figures 5, 7, 8). Interestingly, proteins in the elastinmicrofibril axis (EMILIN1, EMILIN3, FBN1, FBN2, FBN3, and THSD4) [39][40][41] were also elevated in human fetal kidneys compared with the adult, 12 indicating this understudied axis in the kidney warrants further research. 40,41 In contrast with the fibrous structures observed at perinatal timepoints, relatively little interstitial patterning was observed in the adult using our decellularization method ( Figure S11).…”
Section: Discussionmentioning
confidence: 98%
“…Heat-mediated antigen retrieval was performed in a pressurecooker in the appropriate buffers as previously described [42]. A secondary FITC-conjugated goat anti-rabbit IgG (1:250; A-11037, Life Technologies, Darmstadt, Germany) was used.…”
Section: Radial Diffusion (R Diff )mentioning
confidence: 99%